2020
DOI: 10.1002/cpdd.845
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double‐Blind Study Comparing Pharmacokinetics and Pharmacodynamics of Proposed Biosimilar ABP 798 With Rituximab Reference Product in Subjects With Moderate to Severe Rheumatoid Arthritis

Abstract: ABP 798 is a proposed biosimilar to rituximab reference product (RP), an anti-CD20 monoclonal antibody. Pharmacokinetics (PK), pharmacodynamics (PD), and safety results from the comparative clinical study that evaluated the PK, PD, safety, efficacy, and immunogenicity of ABP 798 versus rituximab RP are presented here. Subjects with moderate to severe rheumatoid arthritis (RA) received 2 doses of ABP 798, United States-sourced RP (rituximab US) or European Unionsourced RP (rituximab EU), each consisting of two … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Post-baseline, immunogenicity data for the first dose period have previously been reported [12]. From day 1 through the EOS, 14 (14.4%) subjects in the ABP 798/ ABP 798 group, 13 (13.8%) subjects in the rituximab EU/ rituximab EU group, and 20 (20.6%) subjects in the rituximab US/ABP 798 group developed binding ADAs.…”
Section: Immunogenicitymentioning
confidence: 92%
See 3 more Smart Citations
“…Post-baseline, immunogenicity data for the first dose period have previously been reported [12]. From day 1 through the EOS, 14 (14.4%) subjects in the ABP 798/ ABP 798 group, 13 (13.8%) subjects in the rituximab EU/ rituximab EU group, and 20 (20.6%) subjects in the rituximab US/ABP 798 group developed binding ADAs.…”
Section: Immunogenicitymentioning
confidence: 92%
“…The first dose was admin- Subjects were monitored throughout the study for adverse events (AEs) and concomitant medication use. Clinical laboratory and vital signs were assessed at multiple time points during the study; these data are reported separately [13].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final steps in the development of a biosimilar include comparisons of PK, safety, immunogenicity, and efficacy between the biosimilar and the RP in human clinical trials. The PK/pharmacodynamic (PD) similarity of ABP 798 with rituximab RP has been demonstrated in a three-arm study in patients with rheumatoid arthritis [13]. The current study (JASMINE) was designed to demonstrate the clinical similarity between ABP 798 and rituximab RP in terms of efficacy, PK, PD, safety, and immunogenicity in patients with previously untreated CD20-positive (CD20+), low tumor-burden follicular lymphoma, as an appropriately sensitive population for the demonstration of clinical similarity.…”
Section: Introductionmentioning
confidence: 99%